Polymorphism of STRs 075820, 0135317, and 0165539 in Dusun population - Chyi, Liew Chyi (Universiti Sains Malaysia, 2006)
DNA typing of short tandem repeat (STR) loci is routinely done for DNA analysis in forensic practices. This PCR .. based technique is useful for paternity and personal identification testing. STR technology evaluates the specific loci that found in nuclear DNA which are highly polymorphic in nature. These highly polymorphic markers can be typed from DNA derived from various forensic biological samples. Once the multiple locus profile is established, it intensifies the discrimination between one DNA profile and another. As the number of analyzed loci increases, the probability of a second, unrelated person, excluding identical twins, having the same profile becomes ever unlikely. Therefore, the population data on the distribution of allele frequencies are essential for the estimation of probability of certainty. It would be of benefit for the forensic community to make data on the genetic variation of selected validated loci in as many populations as possible. This study examined the population frequency and genetic diversity of three autosomal STR loci, D7S820, D13S371, and Dl6S539 in Dusun population of Eastern Malaysia. In this study, there was no detectable departure from the Hardy .. Weinberg equilibrium observed for the three STRs loci by the Chi .. square test. The data obtained in present study have been compared with STRs data of various population groups reported in the literature.